2012
DOI: 10.1016/j.brainres.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Acute and prolonged hindlimb exercise elicits different gene expression in motoneurons than sensory neurons after spinal cord injury

Abstract: We examined gene expression in the lumbar spinal cord and the specific response of motoneurons, intermediate gray and proprioceptive sensory neurons after spinal cord injury and exercise of hindlimbs to identify potential molecular processes involved in activity dependent plasticity. Adult female rats received a low thoracic transection and passive cycling exercise for 1 or 4 weeks. Gene expression analysis focused on the neurotrophic factors; brain-derived neurotrophic factor (BDNF), glial cell line-derived n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 66 publications
(85 reference statements)
2
89
1
Order By: Relevance
“…Possible mechanisms of rehabilitation/training-mediated recoveries could be a combination of cellular, molecular, and trophic effects induced within the central nervous system (CNS) (Foret et al, 2010;Houle and Cote, 2013;Kao et al, 2009;Ying et al, 2005). Indeed, previous studies demonstrated exercise-dependent enhancement of neurotrophin production and secretion (Cote et al, 2011;Keeler et al, 2012), corticospinal tract growth and plasticity (Oh et al, 2009), and synaptic plasticity (Flynn et al, 2013). However, studies on the effect of exercise training on morphological, trophic, and synaptic changes in spared motoneurons that are anatomically intact below the level of injury have been emerging (Gazula et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Possible mechanisms of rehabilitation/training-mediated recoveries could be a combination of cellular, molecular, and trophic effects induced within the central nervous system (CNS) (Foret et al, 2010;Houle and Cote, 2013;Kao et al, 2009;Ying et al, 2005). Indeed, previous studies demonstrated exercise-dependent enhancement of neurotrophin production and secretion (Cote et al, 2011;Keeler et al, 2012), corticospinal tract growth and plasticity (Oh et al, 2009), and synaptic plasticity (Flynn et al, 2013). However, studies on the effect of exercise training on morphological, trophic, and synaptic changes in spared motoneurons that are anatomically intact below the level of injury have been emerging (Gazula et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…In adult rats that received a low thoracic spinal transection and PC exercise for 1 or 4 weeks, the gene expression in the lumbar spinal cord as well as the specific response of motoneurons, intermediate gray and proprioceptive sensory neurons was examined to identify potential molecular processes involved in activity dependent plasticity after SCI. 19 Following SCI, motoneurons and intermediate gray displayed small change in mRNA expression, but acute and prolonged exercise increased levels of mRNA for brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor and neurotrophin-4. In dorsal root ganglion neurons, mRNAs for neurotrophic factors and their receptors were largely unaffected by either injury or exercise, while caspase mRNA expression was increased by injury and decreased by exercise.…”
Section: Non-human Experimental Studiesmentioning
confidence: 99%
“…Similarly, in a recent study assessing mRNA and protein changes after transection at 10 and 31 days post injury, whole spinal cord TrkB mRNA was elevated at 10 days post injury, and whole spinal cord NT3 and TrkB protein was elevated at 31 days post injury, with expression differences also observed depending on the location within the parenchyma of the spinal cord (Keeler BE 2012). Table 1 summarizes the findings of recent experiments to facilitate comparison of these results.…”
Section: Discussionmentioning
confidence: 87%
“…However, these have largely focused on time points of less than 6 weeks Liebl, Huang et al 2001;Liebl DJ 2001;Widenfalk J 2001;Qiao and Vizzard 2002;Gulino R 2004;Zvarova, Murray et al 2004;Qiao and Vizzard 2005;Qiao LY 2005;Qian DX 2006;Li XL 2007;Hajebrahimi, Mowla et al 2008;Qian, Zhang et al 2011;Qian DX 2011;Keeler BE 2012). Although valuable for elucidating the role of neurotrophin signaling in the first 6 weeks after SCI, these data are of uncertain value for relating to longer-term post-SCI function.…”
Section: Neurotrophins/trks Expression In Sensorimotor Circuits Aftermentioning
confidence: 99%
See 1 more Smart Citation